The hot and the cold : ills of humans and maize in native Mexico - Chevalier, Jacques M., 1949-; Bain, Andrés Sánchez (Anthropological horizons., 2003)
"In The Hot and the Cold, Jacques Chevalier and Andres Sanchez Bain examine aspects of indigenous world views and myths, and challenge the prevailing notion that hot-cold reasoning in Latin America is a product of the Hippocratic humoral doctrine brought by the Spaniards in the sixteenth century." "Based on extensive field work in southern Veracruz, this innovative study discusses folk tales and stories of illness from indigenous people, and provides explanations that emphasize the close connections between healing practices, milpa (corn field) cultivation, and corn mythology, indicating that human health and the life cycle of the corn plant are governed by the same principles founded on native concepts of the hot and the cold. Notions of what is cold and what is hot influence the ways in which the Nahuas and Zoque-Popolucas of the Sierra de Santa Marta think about their relationship with the land and all entities that surround them, including fellow humans, plants, animals, and spirits. By revealing the connections between ethnomedicine, agriculture, and mythology, Chevalier and Sanchez Bain help clarify puzzling aspects of Mesoamerican religion and symbolic thought, and lead the way towards a better understanding of indigenous perspectives in the modern world."--Jacket